Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Function f(x) = ax^{2}+bx+c, where a, b, and c are some constants. Define functions g and h as follows:
g(x) = f(x+ 1)−f(x)
h(x) = g(x+ 1)−g(x)
Find algebraic form of h(x)
Can anyone explain how to make it step by step?


Sagot :

g(x) = f(x+1) - f(x)
=[ a(x+1)^2+b(x+1)+c ] - [ax^2+bx+c]
=[ a(x^2+2x+1) +bx + b + c ] - [ax^2 + bx + c]
=[ ax^2 + 2ax + a + bx + b + c ] - [ax^2 + bx + c]
= ax^2 + 2ax + a + bx + b + c - ax^2 - bx - c
= 2ax + a + b
Therefore g(x) = 2ax + a + b
h(x) = g(x+1) - g(x)
=2a (x+1) + a + b - [2ax+a+b]
=2ax + 1 + a +b - 2ax - a - b
Therefore h(x) = 1